Design and fabrication of an electrochemical‐based nanofibrous immunosensor for detection of prostate cancer biomarker, PSMA. (15th March 2022) - Rezaei, Zahra; Alemzadeh, Iran; Vossoughi, Manouchehr
Abstract: Convenient medical diagnostics and treatments can replace conventional healthcare procedures because of their fast and profitable applications with reduced infection risk. Meanwhile, early diagnosis of cancer is a leading research subject due to the high fatality rate of the disease and being a vital precursor in the treatment effectiveness. Electrochemical‐based micro‐biosensors are the best candidates for measuring particular biomarker concentrations in body fluids. To address this need, we used a simple fabrication approach to develop an effective immunosensor for the early detection of cancer, in particular prostate cancer. The carbon fibers, obtained from the electrospinning technique, decorate the sensor's working electrode. The available immobilization surface for antibodies doubled by taking advantage of carbon nanofibers. This modification would increase sensor sensitivity and simplify steps of immobilization. Furthermore, the prostate‐specific membrane antigen (PSMA) biomarker, a more reliable substitute for prostate‐specific antigen in prostate cancer diagnosis, was evaluated in cell culture media as a provisional model. Compared to other works, the present sensor uses more accessible materials and simple techniques. Still, it functions reasonably in the linear range of 10–200 ng/ml with the sensitivity of 22.1 pg/ml and detection limit of 9.5 ng/ml without the need for labeling or any other complicated processes. Specific sample concentrations were assessed with sensors and a commercial PSMA ELISA assay kit. According to obtained results, the present sensors have sufficient accuracy in PSMA detection.